Confidence and motivation to help those with a mental health problem: experiences from a study of nursing students completing mental health first aid (MHFA) training - Crawford, Gemma (BMC Med Educ, 2020)
BACKGROUND: Those studying nursing are at greater risk for developing mental health problems than other tertiary students. Mental Health First Aid (MHFA) training may assist students to support peers and build mental health literacy. Understanding motivation to participate in training can identify factors influencing uptake and completion. This paper explores motivators for university nursing students to participate in MHFA training and uses previous experience and confidence in assisting someone with a mental health problem to triangulate data. METHOD: A randomised controlled trial was employed to measure the impact of the course for nursing students at a large Western Australian university. An online survey was administered prior to MHFA training with undergraduate nursing students (n = 140). Thematic analysis of open-ended questions explores motivators to participate and help provided to an individual. Baseline frequencies describe demographics, confidence in helping and exposure to someone with a mental health problem. A Chi Square test compared confidence in helping and exposure to someone with a mental health problem. RESULTS: More than half of participants reported contact with individuals experiencing mental health problems (55%; n = 77); approximately a third (35.8%) reported limited confidence to assist. Those in previous contact with someone with a mental health problem (71.5%; n = 55) were significantly more likely to feel confident in helping (p = 0.044). Mental health literacy, helping others, career and experiences were described as training motivators. CONCLUSION: Exploiting motivators, both intrinsic and extrinsic may increase MHFA training uptake and completion. Tertiary institutions would benefit from policy to embed MHFA training into nursing degrees. The training may have utility for university degrees more broadly. TRIAL REGISTRATION: Australian New Zealand Clinical Trials Registry; ACTRN12614000861651. Registered 11 August 2014 (retrospectively registered).